Comparison of Subcutaneous Ring Block of the Penis with Caudal Epidural Block for Post Circumcision Analgesia in Children - Uddin, Raihan; Khan, MA Salam (Journal of the Bangladesh Society of Anaesthesiologists, 2021)
Background: Pain is an inevitable consequence of circumcision and a number of methods have nowbeen described to ameliorate this. Local anesthetic techniques have been shown to be more effective thansystemic opioids. Objective: This study compared the subcutaneous ring block of the penis with caudal epidural block forpost circumcision analgesia in children. Materials and method: This comparative study was done during the period of January 2020 to December2020 in BIRDEM General Hospital, Dhaka, Bangladesh. A randomized, prospective, blind trial wasconducted comparing caudal epidural blockade (caudal block) with subcutaneous ring block of the penis(penile ring block) in forty healthy boys between three to five years of age undergoing elective circumcision. Results: Subjects receiving caudal block had a longer duration of analgesia (p <0.05), and longer to firstmicturition (p <0.05) but there was no difference in time taken to awaken from anesthesia or spontaneouslywalk unaided. There were no local or systemic complications related to either block and a very lowincidence of vomiting. Conclusion: It is concluded that both techniques are effective. Caudal block is more reliable and providesa longer duration of analgesia but penile ring block is inherently safer and has a lower incidence ofadverse effects. JBSA 2021; 34(1): 50-53